1994
DOI: 10.1002/yea.320100802
|View full text |Cite
|
Sign up to set email alerts
|

In the budding yeast Kluyveromyces marxianus, adenylate cyclase is regulated by Ras protein(s) in vitro

Abstract: The presence of adenylate cyclase activity was first demonstrated in membrane fractions from the budding yeast Kluyveromyces marxianus. The enzyme showed a Mn(2+)- and Mg(2+)-dependent activity, with optimal pH at around 6 as observed in other yeast species. As in Saccharomyces cerevisiae, where adenylate cyclase is regulated by RAS1 and RAS2, we detected a guanyl nucleotide-dependent activity. Interestingly Y13-259 monoclonal antibody, raised against mammalian p21Ha-ras, inhibited Mg2+ plus GTP-gamma-S-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Here we showed that in K. lactis a heterotrimeric G a subunit (Gpa2p) is involved in the regulation of cAMP production. Others have recently shown the possible participation of Ras-like protein(s) in in vitvo regulation of adenylyl cyclase (Verzotti et al, 1994). Now the investigation of the K. lactis cAMP pathway is becoming an important field to assign specific roles to Ras and Gpa2 proteins in the regulation of adenylyl cyclase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Here we showed that in K. lactis a heterotrimeric G a subunit (Gpa2p) is involved in the regulation of cAMP production. Others have recently shown the possible participation of Ras-like protein(s) in in vitvo regulation of adenylyl cyclase (Verzotti et al, 1994). Now the investigation of the K. lactis cAMP pathway is becoming an important field to assign specific roles to Ras and Gpa2 proteins in the regulation of adenylyl cyclase activity.…”
Section: Resultsmentioning
confidence: 99%
“…The present study concerns the induction, purification and characterization of an amine oxidase (KMAO) from the yeast Kluyveromyces marxianus and its partial cDNA sequencing. This microorganism, phylogenetically close to Saccharomyces cerevisiae , has already been studied in order to elucidate its metabolism, biochemistry and genetics (Verzotti, 1994; Siekstele, 1999; Ladrière, 2000; Llorente, 2000; Belloch, 2002; Pinheiro, 2002), for applications (Medeiros, 2000; Meehan, 2000; Kourkoutas, 2002) and especially for its great resistance to high concentrations of metals and its ability to absorb and then to release them (Yazgan, 1993; Aksu, 2000).…”
Section: Introductionmentioning
confidence: 99%